A polymeric micelle with an endosomal pH-sensitivity for intracellular delivery and enhanced antitumor efficacy of hydroxycamptothecin. (1st April 2019) - Pu, Xiaohui; Zhao, Luling; Li, Jia; Song, Rufeng; Wang, Yanling; Yu, Keke; Hou, Xianqiao; Qiao, Peng; Zong, Lanlan; Chang, Sheng
Graphical abstract: Abstract: Amphiphilic poly(ethylene glycol)-imino-poly(benzyl-l -aspartate) (PIPA) and poly(ethylene glycol)-poly(benzyl-l -aspartate) (PPA) block copolymers were synthesized as pH-responsive and pH-nonresponsive copolymers, respectively. Polymer micelles were fabricated by the film dispersion method, and hydroxycamptothecin (HCPT) was physically encapsulated into the micelles. The average diameter of the HCPT-loaded PIPA micelles (PIPAH micelles) was approximately 230 nm, which was slightly smaller than that of the HCPT-loaded PPA micelles (PPAH micelles, approximately 260 nm). The drug-loading content and encapsulation efficiency of the PIPAH micelles (3.33% and 68.89%, respectively) were slightly higher than those of the PPAH micelles (2.90% and 59.68%, respectively). The PIPAH micelles exhibited better colloid stability, storage stability, and plasma stability than the PPAH micelles. Drug release from the PIPAH micelles with imino groups was pH dependent, and more than 75% or 65% of the loaded HCPT was released within 24 h in weakly acidic media (pH 5.0 or 6.0, respectively). An in vitro cell assay demonstrated that the pH-sensitive micelles exhibited potent suppression of cancer cell proliferation and little cytotoxicity on normal cells. Additionally, these micelles could be efficiently internalized by the tumor cells through macropinocytosis- and caveolin-mediated endocytotic pathways. HCPT-loaded micelles had longer circulation time than the HCPT solution in a pharmacokinetic study. In vivo antitumor experiments indicate that the PIPAH micelles had better antitumor efficacy than the pH-insensitive PPAH micelles and the HCPT solution. Therefore, the pH-responsive PIPAH micelles have great potential for high-efficiency delivery of HCPT. Statement of Significance: In this study, a new type of pH-responsive amphiphilic copolymer, poly(ethylene glycol)-imino-poly(benzyl-l -aspartate) (PIPA) block copolymer, was synthesized. This copolymer had then self-assembled to form nanomicelles for tumor intracellular delivery of hydroxycamptothecin (HCPT) for the first time. In in vitro test, the PIPAH micelles exhibited adequate stability and pH-dependent drug release. To one's excitement, the PIPAH micelles exhibited better antitumor efficacy and biosafety than the pH-insensitive micelles (PPAH) and the HCPT solution in in vitro and in vivo antitumor experiments. Therefore, the pH-responsive micelles in this study have significant potential to be used for high-performance delivery of HCPT and potentially for the targeted delivery of other cancer therapeutic agents. The polymer designed in this study can be used as a carrier of poorly soluble drugs or other active ingredients.